Effect of different water qualities on soil properties and plant growth under natural condition - Abd-Elhady, E. S. E.; Al-Ashri, K. M.; Mashour, A. M. A. (2011)
A pot experiments were conducted at the farm of faculty of agric. Al-azhar university, nasr city, cairo, Egypt to study the effect of irrigation by water differed in their qualities (EC, SAR and RSC parameters) on soil characteristics (both physical and chemical) and plant growth.
Includes references.
Summary in Arabic.
1
Keywords: Water quality management; Soils -- Quality; Soil physical chemistry; Plant-soil relationships; Irrigation water -- Environmental aspects; Soils, Salts in -- Research